Local Community Perspectives on Naming the Mbombo Aukhu Tourism Destination in Oladano Village, Nias - Afore Tahir Harefa; Benifaeri Telaumbanua; Asirida Waruwu (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
Each tourism destination has unique characteristics that attract tourists' attention and interest. This research focuses on the naming of the Mbombo Aukhu tourism destination in Oladano village, Idanogawo-Nias subdistrict. The objective is to understand the local community's perspective on the naming of Mbombo Aukhu as a tourism destination. Using qualitative research methods, data were collected through observation and direct interviews with local community members. The findings reveal that the name Mbombo Aukhu originates from the naturally warm spring water in the area, which is believed to contain sulfur. The name "Mbombo Aukhu" is derived from the Nias language, where "Mbombo" translates to "gumbu idano" and "Aukhu" means "aukhu-aukhu." The local community supports this naming as it reflects the unique identity and cultural significance of the destination. The implications of this research highlight the importance of incorporating local cultural and linguistic elements in the naming and development of tourism destinations. Understanding and respecting local perspectives can enhance community support and contribute to the sustainable and socially responsible development of tourism.